The Effect of Composted Oil Palm Empty Bunches on Growth and Yield of Pakchoi Plants in Ultisol Soil (TROPICAL WETLAND JOURNAL, 2024)
Ultisol faces several challenges as agricultural land, including high soil acidity, low organic matter content, macro-nutrient deficiencies, and low cation exchange capacity that need to be addressed. One proposed solution is the use of oil palm empty fruit bunch (EFB/TKKS) compost, which is rich in N, K, and organic C. This compost can improve the physical properties and soil structure, making it a potential alternative for amending Ultisol. Pakchoi, a vegetable rich in vitamins and minerals, has broader stems and leaves compared to regular green mustard. It thrives in various conditions, both lowland and highland, and has a substantial market demand. This research aims to assess the impact of EFB/TKKS compost application on the growth and yield of pakchoi in Ultisol and to determine the optimal dosage. The study employs a Completely Randomized Design (CRD) with one factor, consisting of 5 treatments and 4 replications, totaling 20 experimental units. The treatments include t0 = TKKS compost 0 ton ha-1, t1 = TKKS compost 15 ton ha-1, t2 = TKKS compost 20 ton ha-1, t3 = TKKS compost 25 ton ha-1, and t4 = TKKS compost 30 ton ha-1. The results indicate that the application of TKKS compost significantly influences the growth and yield of pakchoi in Ultisol, with the optimal dosage identified at 20 ton ha-1.